Desigualdad de género y enfermedades profesionales en Bélgica - Laurent Vogel (Universidade do Porto, 2015)
The Belgian occupational diseases compensation system results in massive inequalities between men and women. The compensation of permanent work disabilities caused by occupational diseases represents accounts for the major part of the budget of the Occupational Diseases Fund. On 10 compensated cases, there are approximately 9 men and one woman. This paper develops hypothesis on the legal mechanisms which cause such inequalities. It underlines the role played by medical expertise at collective level (in the definition of a list of occupational diseases) and at individual level (in the decisions of accepting or rejecting workers' claims). The sub-registration of occupational diseases for women contributes to a vicious circle: prevention is less systematically organized in numerous female jobs and this situation strengthens the stereotype that female jobs are at lower risk from the point of view of occupational health.